New data on the distribution of the Caspian whipsnake Dolichophis caspius (Gmelin, 1789) in the West Kazakhstan region of the Republic of Kazakhstan - Akhmedenov, K.M.; Bakiev, A.G.; Kuzovenko, A.E.; Klenina, A.A.; K.M. Akhmedenov, A.G. Bakiev, A.E. Kuzovenko, A.A. Klenina (Karagandy University of the name of acad. E.A. Buketov, 2025)
Information on the distribution of the Caspian whipsnake Dolichophis caspius (Gmelin, 1789) within the West Kazakhstan region of the Republic of Kazakhstan is summarized and possible reasons for its dispersal across the Bokeyorda district in recent decades are discussed. New discoveries of the species have allowed the northeastern boundary of its range to be pushed 20–30 km northward from the previously known habitats of the Caspian snake. The only protected natural area in Kazakhstan where the species is reliably present and, therefore, currently protected is the “Orda” State Nature Reserve of local significance. To ensure the conservation of the species in Kazakhstan, it is desirable to justify and create a new protected natural area — the regional nature monument “Mount Maloe Bogdo”.
Keywords: state nature reserve of local importance “Orda”; specially protected natural areas; Khaki sor; Maloe Bogdo; Bokeyorda district of West Kazakhstan Region; Red Book of the Republic of Kazakhstan; Colubridae; snakes